2016
DOI: 10.1021/acs.est.6b03020
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Chemicals Modulate Polar Bear (Ursus maritimus) Peroxisome Proliferator-Activated Receptor Gamma (PPARG) and Adipogenesis in Vitro

Abstract: We studied interactions between polar bear peroxisome proliferator-activated receptor gamma (pbPPARG) and selected compounds using a luciferase reporter assay and predictions through molecular docking. Furthermore, we studied adipogenesis by liver and adipose tissue extracts from a polar bear and three synthetic mixtures of contaminants in murine 3T3-L1 preadipocytes and polar bear adipose tissue-derived stem cells (pbASCs). PCB153 and p,p'-DDE antagonized pbPPARG, although their predicted receptor-ligand affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 94 publications
5
44
2
Order By: Relevance
“…Previous studies of metabolic effects of POPs on marine mammals have focussed on adults 55,63,64,66 . Concentrations of POPs in adult seals are an order of magnitude greater than those found in pups, with adult seal blubber containing several thousand ∑PCBs (ng/g) 115 compared to the levels detected in the pups here, which were in the hundreds of ng/g range (Table 1).…”
Section: Glucose Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of metabolic effects of POPs on marine mammals have focussed on adults 55,63,64,66 . Concentrations of POPs in adult seals are an order of magnitude greater than those found in pups, with adult seal blubber containing several thousand ∑PCBs (ng/g) 115 compared to the levels detected in the pups here, which were in the hundreds of ng/g range (Table 1).…”
Section: Glucose Uptakementioning
confidence: 99%
“…Experimental studies have demonstrated that POPs can alter adipocyte function in rodents and human cell lines25,104 . POPs are associated with altered adipose and liver expression of metabolic pathway genes in adult polar bears55,66 and ringed seals (Pusa hispida)63,64 , but the functional consequences of such changes for fat tissue have not been identified.Recent experimental studies that replicate environmental or physiological POP concentrations and congener mixtures provide causal evidence of their immunological105 and adipogenic effects91 . Our work builds on these findings by showing that existing POP concentrations in blubber tissue, generated in utero and through lactational transfer, can alter metabolic properties of adipose tissue in young, developing seals.Our data are consistent with experimental studies showing PCB 77, 153 and dioxin reduce glucose and insulin tolerance in mice, guinea pigs (Cavia porcellus),…”
mentioning
confidence: 99%
“…These issues are compounded for marine mammals, which have extensive fat stores, unique requirements for fat deposition and mobilisation, are often of conservation or management importance, but are difficult to access for whole animal experimental work and tissue sampling. Marine mammal cells have been used in short-term experiments 18 , 19 and subcutaneous fat from marine mammals can be obtained with minimal health impact 20 . However, although polar bear ( Ursus maritimus ) adipocytes can be maintained in culture 19 , elephant seal ( Mirounga angustirostris ) stromal vascular fraction cells do not accumulate fat or differentiate using standard protocols 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Marine mammal cells have been used in short-term experiments 18 , 19 and subcutaneous fat from marine mammals can be obtained with minimal health impact 20 . However, although polar bear ( Ursus maritimus ) adipocytes can be maintained in culture 19 , elephant seal ( Mirounga angustirostris ) stromal vascular fraction cells do not accumulate fat or differentiate using standard protocols 21 . Field conditions and tissue volume also make adipocyte preparations challenging.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, adult female polar bear body condition is related to reproductive success (Derocher et al, 2004, Robbins et al, 2012, indicating a potential link between body condition, contaminant load, and reproductive success. Investigating contaminants in relation to body condition is also interesting in that they are associated with altered metabolism in other species (Voltura and French, 2000, Verreault et al, 2007, van Ginneken et al, 2009, and, as shown in a paper published after and thus not included in our systematic literature review, may have the potential to modulate polar bear energy metabolism (Routti et al, 2016). Finally, measures of polar bear diet were included D r a f t in ≤ 9% (≤ 17; Table 3) of the contaminant analyses.…”
Section: R a F Tmentioning
confidence: 99%